The effect of peer education on health beliefs about breast cancer screening - KADIOĞLU, HASİBE (WILEY, 2019)
Aim The aim of this study was to evaluate the effect of peer education about breast cancer screening on the health beliefs of female university students. Background The breast self-examination method is an effective technique that is also simple and inexpensive. Introduction In recent years, besides the classic methods of providing education on breast self-examination, it has been observed that the use of the technique of peer education is increasing and more and more studies are being conducted on this method and its effectiveness. Methods This study is of quasiexperimental design using a single group, pretest/post-test model. The study was conducted with 742 university first-year students. The data for the study were collected using a Sociodemographic Questionnaire, the Breast Cancer Knowledge Questionnaire, Peer Education Satisfaction Questionnaire and Champion's Health Belief Model Scale. Results It was found that the students' perception of barriers to performing the breast self-examination had declined and their self-efficacy had increased, and that the level of perceived barriers to having a mammogram had decreased and 98% of the students were satisfied with the peer education. Conclusion It was seen in this study that the level of knowledge of the students about breast cancer, perceived severity, barriers, benefits and self-efficacy as well as the rate of performing BSE displayed a significant increase after the peer education programme. Implications for nursing and health policy The method of peer education may be utilized in the effort to increase young women's awareness about breast cancer and ensure that they learn about breast self-examinations. The peer education model can be useful in providing breast self-examination education to young people in school. The results of the present study may be beneficial in developing policies on health education on university campuses.
Keywords: Breast Cancer; Early Diagnosis; Health Belief; Peer Education; Self-Examination; Students; SELF-EXAMINATION; TURKISH WOMEN; ADAPTATION; STUDENTS